EFFECT OF THEVETIA PERUVIANA ON MURINE-INDUCED OBESITY - Pérez-García, Ma Dolores; Romero-Cerecero, Ofelia; Zamilpa, Alejandro; Román-Ramos, Rubén; Tortoriello, Jaime (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Obesity is considered a multifactorial disease that has importantly increased the development of chronic degenerative diseases. Drugs available for treating obesity have the inconvenience of producing side effects of importance. In Mexican traditional medicine, the seeds of Thevetia peruviana have been widely employed for weight reduction. Materials and Methods: The effect produced by different extracts of T. peruviana on MonoSodium Glutamate (MSG)-induced obesity in mice was evaluated. A chemical analysis oriented toward the identification of the chemical compounds contained in the active extract was carried out. Results: Oral administration of the hexanic extract of T. peruviana (for 7 weeks) was capable of diminishing weight gain by up to 24.1% in the mice without observing the development of resistance to insulin. Median lethal dose of the hexanic and Ethyl Acetate (EtOAc) extracts was >2 g/kg. By utilizing bio-assay guided fractionation, eight secondary metabolites were purified and characterized. Conclusion: The hexanic extract obtained from Thevetia peruviana seeds was capable of reducing weight gain in mice with induced obesity. In addition, this extract showed good response to the glucose tolerance test, was able to avoid the development of insulin resistance, and also substantially increased serum adiponectin levels. Eight low-polarity compounds were identified in the active fraction. This species could be considered for ongoing investigation as a potential option to reduce obesity